2002
DOI: 10.1108/14630010310812019
|View full text |Cite
|
Sign up to set email alerts
|

The application of BREEAM in corporate real estate: A case study in the design of a city centre office development

Abstract: Buildings are a substantial contributor towards CO2 levels, and design methods to make buildings much more energy efficient are evolving. In the UK, the Building Research Establishment Environmental Assessment Method (BREEAM) has been in operation for over ten years. The scheme is intended to produce a label that distinguishes sustainable developments in the marketplace. This paper uses an in‐depth case study to examine the role of BREEAM in the design and marketing of a city centre office development. The inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Likewise, in case study C when the target was upgraded to 'excellent' from 'very good', the design team tried to acquire more credits, which then had an impact on design, such as the reduction of the number of car parking spaces. This is supported in the study by Holmes and Hudson (2002) who examined the role of Breeam in the design of a city centre development. They found that the achievement of the top Breeam rating in their study was a major driver of the design, although their study was based on a case study aiming for the highest Breeam rating, which at the time was Breeam 'excellent'.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Likewise, in case study C when the target was upgraded to 'excellent' from 'very good', the design team tried to acquire more credits, which then had an impact on design, such as the reduction of the number of car parking spaces. This is supported in the study by Holmes and Hudson (2002) who examined the role of Breeam in the design of a city centre development. They found that the achievement of the top Breeam rating in their study was a major driver of the design, although their study was based on a case study aiming for the highest Breeam rating, which at the time was Breeam 'excellent'.…”
Section: Discussionmentioning
confidence: 94%
“…However, little is known about the effect of Breeam on building design in practice. In one of the few studies on the topic, Holmes and Hudson (2002) examined the effect of Breeam on the design process of an office building in a city centre. Their study stated that the objective of achieving a Breeam 'excellent' rating influenced the original design of the building and the changes made to the design, including building design, water services, landscape design, ventilation services and materials.…”
Section: Background On Assessment Tools and Breeammentioning
confidence: 99%
“…Boschmann and Gabriel () note that only 15 points out of 241 in the six case study buildings they analysed were earned as a result of local design adaptations (what they call ‘deep green’ strategies). Meanwhile, Holmes and Hudson () observe that in the case of BREEAM, materials rated by BRE (the parent company owning BREEAM) are usually used because of the need for particular types of data about their performance, this limiting opportunities for the incorporation of locally unique and sourced methods of cladding, insulation etc. Similarly, Sev () argues that a disproportionately high amount of imported materials are used in buildings assessed by mobile models because of a lack of data on the energy performance of local (traditional) materials.…”
Section: Mobile Sustainable Building Assessment Models: Examining Infmentioning
confidence: 99%
“…According to Wasiluk (2007), sustainable commercial buildings have a competitive advantage over traditional commercial buildings because of their ability to attract higher profile tenants to command above-market rentals and thus, capital values. Furthermore, green buildings command a premium by virtue of the ''badge of honor,'' which is awarded by the rating systems, and the concomitant brand name, which investors use in marketing (e.g., Shiers, 2000;Holmes and Hudson, 2001;Jones Lang LaSalle, 2006;Reed and Wilkinson, 2006). These findings have been replicated by Miller, Spivey, and Florance (2008), who conclude that ENERGY STAR-rated and LEED-certified office buildings in the U.S. have a competitive advantage over their non-rated counterparts.…”
Section: Economic Benefitsmentioning
confidence: 99%